Histoire positive et histoire sacrée autour de la pensée de Louis Massignon - Dominique Avon (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
Louis Massignon (1883-1962) was one of the famous orientalists during the first part of the 20th c. His PHD was based on the life of a mystic Muslim, Mansur al-Hallaj (c. 858-922), who was prosecuted and executed. Three factors explain his influence. First, his erudition combined with an exceptional strength of work which insured him to stay at the top of the discipline. Second, his connexion with the diplomatic services, which warranted him a political support. Third, his capacity to create a new path within the Catholic Church in which he became as much famous as contested. Some of his publications are meaningful of a specific conception in religious sciences. As the example of the “Seven Sleepers of Ephesus” will show, he rejected some results of exegesis or archaeological researches, in the name of a common word crossing religious traditions.